From terrorists to statesmen: terrorism and polish independence - Fischer von Weikersthal, Felicitas (Studies in conflict and terrorism, 2020)
This article examines the legacies of radical and terrorist pasts in Józef Piłsudski's “moral dictatorship” in interwar Poland. Leading figures of Piłsudki's government had been involved in the fight for Polish independence already during the years of the Russian Revolution of 1905. They joined the radical fighting squads of the Polish Socialist Party and participated in acts of political and economic terror. Exploring in detail the terrorist past of these later statesmen this article argues that their terrorist backgrounds were reflected in and shaped the nature of Piłsudki's leadership.
Published online: 30 May 2018
Gesehen am 21.12.2020